Risk Factors for Microscopic Hematuria in Women. Issue 6 (November 2016) - Richter, Lee A.; Lippmann, Quinn K.; Jallad, Karl; Lucas, Joelle; Yeung, Jennifer; Dune, Tanaka; Mellano, Erin; Weissbart, Steven; Mete, Mihriye; Kim, Ja-Hong; Gutman, Robert
Abstract : Objectives: The objective of this study was to determine the risk factors that may contribute to the diagnosis of microscopic hematuria (MH) in women. Methods: This multicenter case-control study reviewed cases of women presenting to Female Pelvic Medicine & Reconstructive Surgery sites with MH from 2010 to 2014. Microscopic hematuria was defined as 3 or more red blood cells per high power field in the absence of infection as indicated in the American Urologic Association guidelines. Controls were matched to cases in a 1:1 ratio and chart review of 10 risk factors was performed (urethral caruncle, pelvic organ prolapse, vaginal atrophy, personal or family history of nephrolithiasis, prior prolapse or incontinence surgery, past or current smoking, chemical exposure, family history of urologic malignancy, prior pelvic radiation, and prior alkylating chemotherapy). Odds ratios were performed to assess risk factors. Results: There were 493 cases and 501 controls from 8 Female Pelvic Medicine & Reconstructive Surgery sites. Current smoking, a history of pelvic radiation, and a history of nephrolithiasis were all significant risk factors for MH ( P < 0.05). Vaginal atrophy, menopausal status, and use of estrogen were not found to be risk factors for MH ( P = 0.42, 0.83, and 0.80, respectively). When stratifying the quantity of MH, women with increased red blood cells per high power field were more likely to have significant findings on their imaging results. Conclusions: Our findings suggest that the risk factors for MH in women are current smoking, a history of pelvic radiation, and a history of nephrolithiasis. Abstract : In a multi-centered case-controlled study, we suggest risk factors for MH in women to be current smoking, a history of pelvic radiation and a history of nephrolithiasis.